2014
DOI: 10.1093/jxb/eru142
|View full text |Cite
|
Sign up to set email alerts
|

Isopentenyltransferase-1 (IPT1) knockout in Physcomitrella together with phylogenetic analyses of IPTs provide insights into evolution of plant cytokinin biosynthesis

Abstract: SummaryIs there more than one pathway for cytokinin biosynthesis in Physcomitrella? Despite the apparent absence of adenylate-isopentenyltransferases, characterization of ipt1 knockout mutants points towards a second, tRNA-independent cytokinin biosynthesis pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 71 publications
5
59
0
Order By: Relevance
“…Nevertheless, the iP-type and tZ-type cytokinins are still present and are also the most active forms in this moss (28). In a recent study, it was also suggested that a tRNA-independent pathway exists in case of P. patens (29). Therefore, it may be that the nematode tRNA-IPT enzyme catalyzes the production of a broader range of cytokinins.…”
Section: Discussionmentioning
confidence: 90%
“…Nevertheless, the iP-type and tZ-type cytokinins are still present and are also the most active forms in this moss (28). In a recent study, it was also suggested that a tRNA-independent pathway exists in case of P. patens (29). Therefore, it may be that the nematode tRNA-IPT enzyme catalyzes the production of a broader range of cytokinins.…”
Section: Discussionmentioning
confidence: 90%
“…The ancient pathways for auxin (Bennett et al 2014a(Bennett et al , 2014bFinet and Jaillais 2012;Paponov et al 2009), cytokinin (Lindner et al 2014;Pils and Heyl 2009;von Schwartzenberg et al 2007), and ethylene (Yasumura et al 2012) were investigated with respect to their corresponding transporters, biosynthesis, and signaling pathways. Further, moss is lacking essential characteristics of the classical gibberellin signaling pathway, although it responds to external gibberellin treatment (Vandenbussche et al 2007).…”
Section: Several Regulatory Pathways Evolved In the Common Ancestor Omentioning
confidence: 99%
“…The activity of tRNA‐IPT and an associated tRNA degradation process represents a conserved mechanism for CK production and accounts for the major portion of c Z in A. thaliana and P. patens (Miyawaki et al ., ; Lindner et al ., ). Consistently, homologous proteins have been identified in all living organisms, except Archaea (Spíchal, ).…”
Section: Discussionmentioning
confidence: 97%
“…This modification stabilizes codon-anticodon binding and thus enables precise protein biosynthesis (Konevega et al, 2006). The degradation of these modified tRNAs accounts for the major pool of cZ-type CKs in Arabidopsis thaliana and the moss Physcomitrella patens (Miyawaki et al, 2006;Lindner et al, 2014).…”
Section: Introductionmentioning
confidence: 99%